P PENINGKATAN PEMAHAMAN MEMBACA DAN MINAT BELAJAR BAHASA INDONESIA MELALUI MEDIA KOMIK DIGITAL DI KELAS V SEKOLAH DASAR: KOMIK DIGITAL - Ramiyati Ramiyati; Haryadi; Bernadus Wahyudi Joko Santoso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the improvement of reading comprehension and learning interest in Indonesian language through the use of digital comic media among fifth-grade elementary school students. The research was motivated by the low level of student engagement and motivation in reading activities, as well as the limited availability of engaging learning media that suits the developmental characteristics of young learners. This research employed a classroom action research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 15 fifth-grade students from a public elementary school. Data on reading comprehension were collected through evaluation tests at the end of each cycle, while data on learning interest were obtained through questionnaires and observation sheets. The results showed that the use of digital comics improved students’ reading comprehension, as indicated by the increase in the average test scores across the cycles. In addition, students’ learning interest also increased, reflected in their growing enthusiasm, attention, and active participation during the learning process. Therefore, digital comics are proven to be an effective alternative learning medium for improving reading comprehension and learning interest in Indonesian language instruction at the elementary school level.